Effective School Management Through Total Quality Management - Venalia, Agantina; Siti Dwiningrum; Burgawanti (Tahta Media Group, 2024)
Realizing the quality of education that is good and remains controlled, there must be a national standard of school management. The purpose of this research is to analyze and describe in depth, through a literature review, effective school management through Total Quality Management (TQM). The study employs a qualitative method; the data is collected using a literature review that is critically and comprehensively reviewed. TQM in program implementation requires high commitment from the members or individuals involved. The eight TQM components should ensure the success of its activities. School principals play an important role because they must be able to develop, train, and implement these eight components in the implementation of educational programmes in schools. TQM will fail if it is not based on ethics, integrity and trust. Training for TQM empowerment as well as specific technical skills are essential for program implementation as they can create a work environment conducive to program objectives. The lack of communication between sections and implementers can be a burden or obstacle in the implementation of activities.